Transient Voltage-Reactive Power Modeling of Offshore Wind Power Collection and Transmission System with AC Cables and Characteristic Analysis - Yanxia SUN; Shiwen FANG; Zhen LI (Zhongguo dianli)
The transient overvoltage at the sending terminal of the offshore wind power collection and transmission system with AC cables threatens the safe and stable operation of the system. To quantitatively analyze the impact of transient voltage on offshore wind turbines and thereby guide the configuration of the voltage-reactive power control system for offshore wind power, we need to develop a transient voltage-reactive power model of the offshore wind power collection and transmission system with AC cables as soon as possible. This paper approaches this problem by analyzing the characteristics of the equivalent network of the transmission system considering AC cables and clarifying the boundary conditions for the equivalent network to demonstrate inductive characteristics or capacitive ones. Then, for the case of the equivalent network displaying capacitive characteristics, we build a mathematical transient voltage-reactive power model of offshore wind power considering AC cables and verify the validity of the mathematical model on the control hardware in the loop (CHIL) based real-time simulation experiment platform. Finally, with the transient voltage-reactive power model of offshore wind power, we quantitatively analyze the influences of AC cable line length and the control bandwidth and damping ratio of the current loop in the wind turbine grid-side converter (GSC) on transient overvoltage at the generator terminal to lay a theoretical foundation for quantitatively assessing the risk of transient overvoltage in the offshore wind power collection and transmission system with AC cables.